Chinatown Growth in Surakarta from The Colonial Era to The Millennium Era (XVIII-XX Century) - Inayati Fatimah (Sinolingua: Journal of Chinese Studies, 2023)
Chinatown is an area inhabited by Chinese. The old Chinatown is characterized by rows of shophouse facing each other with curved tiled roof with Chinese ornaments. This typical Chinatown building are disappearing as a city develop, replaced by modern buildings. The old typical Chinatown in Surakarta is concentrated in Kampung Sudiroprajan. The purpose of this study is to find out the Chinatown growth since the birth of Surakarta until present and what factors have influenced its growth. The method used in this research is descriptive qualitative method using archival data sources, literature review and map observation. City theory is used to understand the city and Chinatown growth. The data was then analyzed using a comparative study with the technique of comparing three maps of Chinatown from three different periodizations: Colonial, Old Order-New Order and reform to present. The findings is that the Chinatown growth is influenced by political factors, it is a regime’s policy towards the Chinese community. The Surakarta Chinatown continued to grow organically around economic, business and trade nodes and approaching main transportation path and nodes. Its landmark is a temple. Chinatown inhabitant is not only Chinese, there are natives and other ethnicities. The biggest Chinatown growth is around Solo's golden triangle, namely around Gede Market, Klewer Market and Legi Market. It also grows around Solo City landmark, the North-South cosmological axis in Kasunanan Palace. The second rapid growth is in the Solo Baru. The trading image of Chinatown was overlap with the cultural image of Solo City.